Regional Financial Spillovers Across Europe : A Global VAR Analysis - Sgherri, Silvia (IMF Working Papers; Working Paper ;, 2009)
The recent financial crisis raises important issues about the transmission of financial shocks across borders. In this paper, a global vector autoregressive (GVAR) model is constructed to assess the relevance of international spillovers following a historical slowdown in U.S. equity prices. The GVAR model contains 27 country-specific models, including the United States, 17 European advanced economies, and 9 European emerging economies. Each country model is linked to the others by a set of country-specific foreign variables, computed using bilateral bank lending exposures. Results reveal considerable comovements of equity prices across mature financial markets. However, the effects on credit growth are found to be country-specific. Evidence indicates that asset prices are the main channel through which-in the short run-financial shocks are transmitted internationally, while the contribution of other variables-like the cost and quantity of credit-becomes more important over longer horizons.